Knowledge of Primary Care Physicians on Lysosomal Storage Disorders - Engin Köse; Selda Bülbül; Nur Arslan (Galenos Yayinevi, 2019)
Aim:Since patients with lysosomal storage disorders (LSDs) often apply to primary care physicians initially, these doctors play a crucial role in the early diagnosis of LSDs. In this study, we aimed to determine the knowledge and awareness of primary care physicians regarding LSDs.Materials and Methods:We conducted a survey between January 2016 and April 2016 among primary care physicians from various regions of Turkey. Invitation e-mail was randomly sent to the individual e-mail address of each physician for a web-based survey. The questionnaire globally consisted of three sections with a total of 30 questions. In the first part of the survey, demographic characteristics of physicians (age, gender, career information) were recorded. The second section consisted of questions on LSDs for the evaluation of knowledge among physicians. In the third section of survey, questions were about the reasons of insufficient knowledge on LSDs and possible solutions to raise awareness.Results:A total of 261 primary care physicians [109 females (41.8%), mean age 40.1±8.8 years] were enrolled in the study. The mean working time was 14.9±8.6 years. Among the participants, 75.8% and 88.8% stated that they had never encountered an LSD patient before and never considered LSDs as a differential diagnosis for any patient, respectively. Fifteen percent of physicians stated that they had no idea about the clinical findings and symptoms of LSD. Another 26.2% of the participants stated that LSD is screened during the neonatal screening program in Turkey. Mean "total knowledge score" of the physicians was 13.47±5.85 points [median=15.0 (10.5-18.0)] out of 25. Six (2.3%) primary care physicians had a total score of "0". Only 1 of them scored "25" points.Conclusion:Knowledge of primary care physicians on LSDs is not satisfactory in Turkey. Undergraduate medical education and postgraduate educations play a key role to raise awareness.